2015
DOI: 10.5812/jjm.8(4)2015.16236
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Fermentation Conditions for Recombinant Human Interferon Beta Production by Escherichia coli Using the Response Surface Methodology

Abstract: Background:The periplasmic overexpression of recombinant human interferon beta (rhIFN-β)-1b using a synthetic gene in Escherichia coli BL21 (DE3) was optimized in shake flasks using Response Surface Methodology (RSM) based on the Box-Behnken Design (BBD).Objectives:This study aimed to predict and develop the optimal fermentation conditions for periplasmic expression of rhIFN-β-1b in shake flasks whilst keeping the acetate excretion as the lowest amount and exploit the best results condition for rhIFN-β in a be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…13 Culture medium determines the nutritional and chemical environment of microorganisms during cultivation. 14 Hence, investigation regarding the physiologic and metabolic changes in the microalgal cells, their growth pattern and also their composition during nutrient limitation in culture medium is of importance. The obtained data could be employed to increase the growth rates and also improve the β-carotene production process.…”
Section: Introductionmentioning
confidence: 99%
“…13 Culture medium determines the nutritional and chemical environment of microorganisms during cultivation. 14 Hence, investigation regarding the physiologic and metabolic changes in the microalgal cells, their growth pattern and also their composition during nutrient limitation in culture medium is of importance. The obtained data could be employed to increase the growth rates and also improve the β-carotene production process.…”
Section: Introductionmentioning
confidence: 99%
“…The recombinant human interferon beta (rhIFN-β)-1b was optimized in shake flasks using response surface methodology (RSM). The production of rhIFN-β-1b was significantly increased using the optimized conditions, and the rhIFN-β production was increased from 0.255 g·L −1 to 0.981 g·L −1 [ 14 ]. In our present study, we use this approach to improve the fermentation conditions of CS5931, and the results show that the production of CS5931 is greatly increased; the yield of the purified polypeptide was increased from 2.0 mg/L to 7.5 mg/L.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study indicated that glycoprotein GP-1 production was strongly affected by medium components, especially the types and concentrations of carbon and nitrogen sources [ 14 ]. Process factors (temperature, pH, rotating speed) also play an important role in improving objective metabolites production and may contribute to the reduction of fermentation cost, even changing the path of microbial biosynthesis to discover new natural products [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%